Calotropis procera (Ait.) Apocynaceae grown on organic substrates - Moreira, Francisco José Carvalho; Menezes, Ademir Silva; Nascimento, Francisco Mikael Oliveira; Silva, Maria Elisâgela Souza; Pinheiro Neto, Luis Gonzaga (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
There are several sources of organic inputs that can be used in the agricultural environment for the production of seedlings. The objective of this work was to evaluate the percentage of emergence of jealous seedlings (Calotropis procera) and their initial growth in different substrates, in order to determine which of the substrates presents the best behavior for this species. The experiment was conducted at the Federal Institute of Ceará Campus Sobral, with twelve sand substrates; Ground; Goat manure; Bagana; coconut fiber; Sand + manure; Sand + coconut fiber; Sand + bagana; Soil + goat manure; Solo + coconut fiber; Solo + bagana; Soil + goat manure + bagana) with four replicates. The percentage of emergence, plant height, stem diameter and leaf number, root length, dry shoot mass and root dry mass of jealous plants were measured. The substrates when combined with coconut fiber, bagana and goat manure provide better conditions of vigor and better development of the aerial part of the plants of jealousy. The substrates considered not ideal for emergence of C. procera seedlings are manure goat and soil + goat manure.